2015
DOI: 10.1097/tp.0000000000000357
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Preemptive Renal Transplantation

Abstract: The principle barrier to renal transplantation referral before dialysis was patient education regarding the option of preemptive transplantation. Factors significantly associated with referral before dialysis were the diagnosis of polycystic kidney disease, white recipient race, referral by a transplant nephrologist, and employed status. Greater effort should be applied to patient education regarding preemptive transplantation early after the diagnosis of end-stage renal disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 13 publications
(13 reference statements)
0
21
0
Order By: Relevance
“…Similarly, educational level and insurance status did not affect the rate of PreKTx. Knight and colleagues 13 also reported the importance of patient education to achieve PreKTx, though their data also emphasized referral by a transplant nephrologist. In the current study, individual self-identified barriers to transplantation did not adversely affect the rate of PreKTx, but the presence of multiple self-identified barriers was more strongly associated with non-PreKTx.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, educational level and insurance status did not affect the rate of PreKTx. Knight and colleagues 13 also reported the importance of patient education to achieve PreKTx, though their data also emphasized referral by a transplant nephrologist. In the current study, individual self-identified barriers to transplantation did not adversely affect the rate of PreKTx, but the presence of multiple self-identified barriers was more strongly associated with non-PreKTx.…”
Section: Discussionmentioning
confidence: 99%
“… 12 Prior studies have also emphasized the importance of early patient education by providers as a means of increasing rates of PreKTx. 13 Indeed, focused interventions consisting of specialized chronic kidney disease clinics have been able to increase the number of eligible patients referred for transplant, including a large number of preemptive referrals. 14 However, few studies have asked patients themselves about their perceived barriers to achieving PreKTx.…”
mentioning
confidence: 99%
“…This is in keeping with previous research that suggests that socioeconomically deprived individuals are less likely to receive a pre-emptive kidney transplant. 17,18,[47][48][49] This may reflect the association of SED with more rapid progression of renal disease towards renal failure, 50 later presentation to secondary care 51,52 and later listing for transplantation. 43,44,53,54 Qualitative work also suggests that a lack of a long-term health perspective might mean that LDKTs aren't considered until a situation makes it of importance in the short-term.…”
Section: Socioeconomic Deprivation and Living Kidney Donationmentioning
confidence: 99%
“…11 As education about transplantation has not yet been standardized, 45 use of Infórmate may help to achieve that aim. As education is pivotal to increasing preemptive transplantation, 46 patients with ESRD should be provided with as much education as possible prior to initiating renal replacement therapy. Communicating about the availability of Infórmate early in patients' chronic kidney disease (CKD) may foster preemptive transplantation.…”
Section: Discussionmentioning
confidence: 99%